BEBERAPA SIFAT KIMIA TANAH DI BAWAH TEGAKAN NYATOH (Palaquium obtusifolium Burck) DI DESA SINDOSA KECAMATAN SINDUE TOBATA KABUPATEN DONGGALA - Ibrahim, Yusnita; Yusran, Yusran; Umar, Husain (ForestSains, 2018)
Nyatoh (Palaquium obtusifolium Burck) is a type of tree that is very much in demand by local and international communities. Nyatoh stands (Palaquium obtusifolium Burck) which is adjacent to the agricultural crops owned by residents in the village, is interesting because it will show that, the level of soil fertility is influenced by vegetation. Not only that, according to local residents, after the land was planted with Nyatoh plants (Palaquium obtusifolium Burck) erosion and landslides had not occurred again.The research was conducted from October to December 2017 located in the village of Sindosa, Sindue Tobata district, Donggala district. This research was started from a field survey, determination of sampling points, soil sampling and analysis of soil samples in the laboratory of the Faculty of Agriculture, University of Tadulako. Soil sampling is done by taking intact soil samples at several predetermined locations namely peaks, backs, and valleys. Each slope is determined by 5 soil sampling points to represent each location with 2 types of depth, namely 0-30 cm and 30-60 cm. Then the samples obtained from these 5 points will be compiled. From the three locations there were 30 soil samples before they were compiled. Overall soil samples after being compiled will get 6 soil samples analyzed at the Soil Science Laboratory of the Faculty of Agriculture to determine the chemical condition of the soil. Data obtained from the laboratory are then analyzed descriptively, namely by describing the chemical properties of the soil, namely pH, CEC, C-Organic and soil organic matter.The results showed an average pH with a depth of 0-30 cm, which is 6.64, while at a depth of 30-60 cm showed a pH with an average of 6.43, Cation Exchange Capacity (CEC) on average below the Nyato stand at Sindosa village Sindue Tobata District Donggala Regency at a depth of 0-30 cm, which is 25.87 (cmol (+) kg Â¹) is in the medium category, while at a depth of 30-60 cm is 3.23 (cmol (+) kg kedalaman Â¹) belongs to the very low category. The C-Organic content at a depth of 0-30 cm with an average of 2.45 is included in the medium category and at a depth of 30-60 cm that is 0.65, including very low. The content of Soil Organic Materials (BOT) with an average depth of 0-30 cm, which is 4.23 included in the high category and at a depth of 30-60 cm with an average of 1.11 is low.